1969
DOI: 10.1029/ja074i016p03969
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of electrostatic proton cyclotron harmonic waves from Alouette 2 satellite data

Abstract: An ELF noise band observed by the Alouette 2 receiver has been analyzed using digital power spectrum techniques. Detailed spectra indicate that for altitudes 500–3000 km and all geomagnetic latitudes sharp lower frequency cutoffs of the noise band occur very near to the calculated proton gyrofrequency. Further spectral characteristics are pointed out. All aspects of the noise band are interpreted in terms of ambient electrostatic proton cyclotron harmonic waves. In particular, this hypothesis explains such fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…When the proton gyroradius becomes comparable to the transverse wavelength, however, proton harmonic waves propagate in the plasma. This propagation may explain the recent observations of proton harmonic resonances observed in the ionosphere with Ogo 2 [Guthart et al, 1968] and with Alouette 2 [Harvey, 1969] and in an auroral zone rocket flight . DISPERSION…”
supporting
confidence: 60%
“…When the proton gyroradius becomes comparable to the transverse wavelength, however, proton harmonic waves propagate in the plasma. This propagation may explain the recent observations of proton harmonic resonances observed in the ionosphere with Ogo 2 [Guthart et al, 1968] and with Alouette 2 [Harvey, 1969] and in an auroral zone rocket flight . DISPERSION…”
supporting
confidence: 60%
“…Bell et al [1983] have also suggested that impulsive ELF hiss often associated with spectral broadening may be electrostatic. Harvey [1969] has indicated that ELF noise band with sharp lower-frequency cutoffs slightly above the local proton gyrofrequency and somewhat gradual upper cutoffs was frequently observed by Alouette 2 satellite during low-and middle-latitude passes and that the observed result could be explained by the hypothesis that the noise band was due to electrostatic proton cyclotron EH) field data at 0423 UT, August 11, 1982, where f•, is input transmitter signal frequency, ft. frequency of ELF emissions coupled, fn-t. and b:(k, --L) lower sideband frequency and bicoherence value, fn+t• and b:(k, L) upper sideband frequency and bicoherence value, and f,, proton gyrofrequency…”
Section: Structurementioning
confidence: 93%
“…To investigate this hypothesis further, the characteristics of the noise found in these two principal regions were studied by means of two different types of spectral analysis. In the first of these analyses the broadband output of the receiver was digitized and the spectrum calculated with a digital computer by using a fast Fourier transform routine [Harvey, 1969]. Two examples of the spectra produced in this fashion are shown in Figure 5.…”
Section: Vlf No•se Lewlsmentioning
confidence: 99%
“…The ELF noise bands, such as those shown in Figure 5 below 1 kHz, generally appear to be the strongest spectral components in the broadband output of the VLF receiver. They usually exhibit a sharp lower-frequency cutoff near the proton gyrofrequency but do not always have a distinct upper-frequency limit [Harvey, 1969]. ELF noise bands are easy to recognize in the film records, exemplified in Figure 6, produced by the Rayspan spectrum analyzer.…”
Section: Observations Of Elf Noisementioning
confidence: 99%